Ecological Value of Bird Diversity in the Buffer City Area of Indonesia’s New Capital, East Kalimantan - Agil, Muhamad; Hidayah, Maulida Ulfa; Kadir, Marniati (Jurnal Sylva Lestari, 2025)
The development of Indonesia’s new capital will impact the lives of living things, including birds. This study aims to determine the bird species diversity in the buffer cities surrounding Indonesia’s new capital area, specifically in Tenggarong, Samarinda, Balikpapan, and Penajam. Bird data were collected using the point count method. The results showed that the bird diversity index (H') in these cities falls within the medium category, with the highest value recorded in Tenggarong (H' = 2.23) and the lowest in Balikpapan (H' = 1.85). The most abundant species were Hirundo tahitica in Tenggarong (23.65%) and Balikpapan (23.65%), and Passer montanus in Samarinda (28.75%). In Penajam, both P. montanus and Pycnonotus aurigaster showed the highest relative abundance (21.9%). The evenness index ranged from 0.72 to 0.77 across the four cities, while species richness was categorized as medium in Tenggarong, Samarinda, and Penajam, but low in Balikpapan. Among the 34 bird species identified, 32 were classified as Least Concern (LC), one as Vulnerable (VU), and one as Endangered (EN) according to according to the International Union for Conservation of Nature (IUCN) Red List of Threatened Species. To safeguard the survival of birds in buffer cities, especially those categorized as VU and EN, both the government and local communities must implement targeted conservation policies, preserve natural habitats, and promote sustainable ecological practices. Keywords: bird, buffer city, conservation, diversity, Indonesia’s new capital